2020
DOI: 10.1088/1742-6596/1572/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Effect size test of 7e learning cycle model: conceptual understanding and science process skills on senior high school students

Abstract: This study aims to determine the effectiveness of the 7E Learning Cycle Model of conceptual understanding and science process skills students. The research method used a quasi-experiment with a non-equivalent control group design. The population in this study were students of class XI IPA Senior High School 9 Bandar Lampung. From the analysis of the hypothesis test showed that t-count obtained a result of 4.838 while t-table of 2.002 according to the provisions if the value of t-count> t-table then H0 was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Beberapa faktor yang memengaruhi pemahaman konsep fisika melibatkan kompleksitas materi pembelajaran, metode pengajaran yang digunakan, serta karakteristik individual siswa (Komikesari et al, 2020). Pemahaman konsep fisika memerlukan integritas konsep yang kuat, yaitu kemampuan untuk mengaitkan, mengorganisir, dan menggeneralisasi konsep-konsep fisika yang dipelajari.…”
Section: Pendahuluanunclassified
“…Beberapa faktor yang memengaruhi pemahaman konsep fisika melibatkan kompleksitas materi pembelajaran, metode pengajaran yang digunakan, serta karakteristik individual siswa (Komikesari et al, 2020). Pemahaman konsep fisika memerlukan integritas konsep yang kuat, yaitu kemampuan untuk mengaitkan, mengorganisir, dan menggeneralisasi konsep-konsep fisika yang dipelajari.…”
Section: Pendahuluanunclassified
“…Several studies have been carried out on the effectiveness of constructivist teaching approaches on students' learning. The studies about the instructions based on the learning cycle model showed that learning cycle approaches help students improve academic achievement (Khan et al, 2020); self-efficacy (Puspita & Fardillah, 2021); critical thinking skills (Marfilinda et al, 2020;Tecson et al, 2021); retention (Abdullahi et al, 2021;Wodaj & Belay, 2021); science process skills (Khairani et al, 2021;Komikesari et al, 2020;Silitonga et al, 2021) and attitudes toward science (Abdullahi et al, 2021;Ören & Tezcan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of research on learning cycle approaches has demonstrated their effectiveness on conceptual understanding (Baybars & Kucukozer, 2018;Gök, 2014;Komikesari et al, 2020;Yilmaz et al, 2011). For example, Gök (2014) investigated the relative effects of 7E learning cycle instruction and curriculum-oriented science instruction on middle school students' conceptual understanding of human body systems in Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other factors that influence the understanding of low learning outcomes involve the complexity of learning materials, teaching methods and models applied, and individual characteristics of students (Komikesari et al, 2020). Understanding physics concepts requires strong concept integrity, that is, the ability to associate, organize, and generalize the physics concepts studied.…”
Section: Introductionmentioning
confidence: 99%